Molecular Study for Detection of Cutaneous Leishmaniasis by Nested PCR in Wasit Province, Iraq - Kadhem, Zainab Abdalameer; Oudah, Abbas Jameel (American Journal of Biology and Natural Sciences, 2025)
Cutaneous leishmaniasis (CL) is an ignored parasitic condition of main clinical interest, which is spread by a parasite, and the disease has a high morbidity in the endemic regions, including Iraq. It is brought about by numerous genera of the genus Leishmania and is contracted by the bite of an infected female phlebotomine sand fly. Treatment options, epidemiological surveillance, and control need to make the appropriate identification of the causative species. This paper utilizes Nested Polymerase Chain Reaction (Nested-PCR) with the use of the kinetoplast DNA (kDNA) as a molecular identification technique of Leishmania species of CL in the Wasit Province, Iraq. This study involved 50 clinically suspected CL patients participating in this study; they were enrolled in Al-Zahra Teaching Hospital and Al-Karamah Teaching Hospital, during the time frame of November 2024 to February 2025. Samples of the skin lesion obtained in little samples were taken across the open body parts and subjected to the Nested-PCR amplification and genomic DNA isolation. The results indicated that 20 samples out of the 50 (40 percent) were positive to the Leishmania DNA and 30 samples out of the 50 (60 percent) were negative. Among the positive cases, 15 (30) cases were Leishmania major and 5 cases (10) Leishmania tropica. Agarose gel electrophoresis revealed standard L. major and L. tropica bands of 560 bp and 750 bp respectively. The findings confirm the hypothesis that the L. major is the most widespread causative agent of CL in Wasit Province. The paper determines that the Nested-PCR is considerably sensitive and specific and would be reliable in the diagnosis of species of Leishmania and their differentiation and should be applied as a routine diagnosis tool as well as in epidemiological research in endemic regions.